1990
DOI: 10.1093/oxfordjournals.humrep.a137181
|View full text |Cite
|
Sign up to set email alerts
|

Endovaginal sonography for the early diagnosis of intrauterine and ectopic pregnancies

Abstract: Endovaginal sonography, together with beta-HCG titre, was used to diagnose ectopic pregnancy in 58 patients. Transabdominal ultrasound failed to conclude this diagnosis. The data from endovaginal sonography revealed the presence of a gestational sac in all 15 patients with normal pregnancies at a beta-HCG level of 1042 mIU/ml. Of the 23 patients with pathological pregnancies only 61% had an intrauterine gestational sac. Only 15% of the 20 patients with ectopic pregnancies showed an increase in beta-HCG greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…With the advent of transvaginal ultrasound, the hCG cutoff has decreased to 1000 -2000 IU/L (12 ). Although the introduction of this hCG discriminatory zone appears effective, a particular hCG concentration has yet to be defined as a good diagnostic indicator for ectopic pregnancy (13 ).…”
mentioning
confidence: 99%
“…With the advent of transvaginal ultrasound, the hCG cutoff has decreased to 1000 -2000 IU/L (12 ). Although the introduction of this hCG discriminatory zone appears effective, a particular hCG concentration has yet to be defined as a good diagnostic indicator for ectopic pregnancy (13 ).…”
mentioning
confidence: 99%
“…An intrauterine pregnancy can be visualized using TVS with serum β -HCG levels as low as 1000 IU/L [9]. In cases of chronic ectopic pregnancy, serum β -HCG levels are usually much lower due to a very small amount of live villi [10].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] This is the first study directly to evaluate and compare sensitivity, accuracy, and predictive value of ultrasound for diagnosing women with symptomatic early pregnancy on the basis of initial ␤-hCG values above or below an established discriminatory zone. A MEDLINE search of the English literature from 1966 to December 1998 using the search terms "ultrasound," "ectopic pregnancy," and "diagnosis" showed that all previous studies evaluated diagnoses of complications of early pregnancy in subjects with a ␤-hCG above the discriminatory zone or did not stratify results on the basis of initial ␤-hCG levels.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Ultrasound in conjunction with serum ␤-hCG concentrations is well established using a discriminatory zone. [5][6][7][8][9] Ultrasound alone has high sensitivity and specificity in diagnosing ectopic pregnancy in high-risk women. If ␤-hCG concentration is above the discriminatory zone, and an intrauterine sac is not seen, abnormal gestation or ectopic pregnancy is considered strongly.…”
mentioning
confidence: 99%
See 1 more Smart Citation